Coalbed Methane Potential Evaluation and Development Sweet Spot Prediction Based on the Analysis of Development Geological Conditions in Yangjiapo Block, Eastern Ordos Basin, China. (25th September 2021) - Fu, Xinyu; Meng, Yanjun; Li, Zhongcheng; Kong, Peng; Chang, Suoliang; Yan, Taotao; Liu, Yanfei
Abstract : The evaluation and prediction of favorable coalbed methane (CBM) sweet spot play an important role in well location deployment and recovery prediction in CBM blocks. This work investigates the CBM geology and accumulation characteristics of No. (8 + 9 ) coal in the Carboniferous Taiyuan Formation in Yangjiapo block based on data from 14 CBM wells. The desorption index is proposed to be used to study the CBM desorption potential in Yangjiapo block, and the parameter of reduced water level is adopted to study the CBM hydrodynamics of the block. Furthermore, the analytical hierarchy fuzzy evaluation method is used to evaluate and prediction the CBM development sweet spot in Yangjiapo block. The results show that the buried depth of the No. (8 + 9 ) coal seam in Yangjiapo block varies from 693.20 to 1213.20 m, the coal thickness is from 5.40 to 13.10 m, the gas content is from 5.89 to 10.55 m 3 /t, and the minimum horizontal principal stress is from 9.80 to 20.82 MPa. The desorption potential is better in the southeastern and central-western part of the block. It is found that there is a positive relationship between CBM content and hydrodynamics and indicated that CBM easily concentrates in the lower reduced water level area. The CBM favorable development sweet spot is forecasted to be located in the southeastern part, central-western region, and northeastern part of Yangjiapo block.